Single plasmonic nanoparticles for biosensing - Sannomiya, Takumi; Vörös, Janos (Trends in biotechnology (Regular ed.), 2011)
Along with remarkable progress of nanoplasmonics over the past 10 years, single plasmonic nanoparticle sensors have introduced a completely new dimension to the sensing scale, considering that nanoparticles are comparable in size to biomolecules such as nucleic acids or antibodies. Single particle sensing methods have recently shown the possibility of detecting the adsorption of single biomolecules, and have already provided information about conformational changes of single molecules. For practical application, arrays of such compact sensor units are expected to realize massive multiplexing and high throughput in diagnostics and drug discovery in the near future. In this review, recent achievements and perspectives of this emerging biosensing technique are discussed.